Separation of Benzene from Linear Alkanes (C-6-C-9) Using 1-Ethyl-3-Methylimidazolium Ethylsulfate at T=298.15 K - Emilio J. González (2010)
In this work, the ionic liquid 1-ethyl-3-methylimidazolium ethylsulfate, [EMim][ESO4], is used to separate benzene from alkanes (hexane, heptane, octane, nonane) by solvent extraction through the study of the liquidliquid equilibria of the ternary systems at T = 298.15 K and atmospheric pressure. The selectivity, solute distribution ratio, and percent removal of the aromatic, calculated from the tie-line data, were used to determine whether this ionic liquid is a good solvent for the extraction of benzene from alkane compounds. The consistency of the tie-line data was ascertained by applying the Othmer-Tobias equation, and the experimental results for the ternary systems were correlated with the nonrandom two-liquid (NRTL) and the universal quasi-chemical (UNIQUAC) models.